The combination of endobronchial elastography and sonographic findings during endobronchial ultrasound‐guided transbronchial needle aspiration for predicting nodal metastasis - Taiki Fujiwara; Takahiro Nakajima; Terunaga Inage; Yuki Sata; Yuichi Sakairi; Hajime Tamura; Hironobu Wada; Hidemi Suzuki; Masako Chiyo; Ichiro Yoshino (Thoracic Cancer, 2019)
Abstract Background During endobronchial ultrasound‐guided transbronchial needle aspiration (EBUS‐TBNA), the sonographic findings of B‐mode imaging, as well as endobronchial elastography, can be obtained noninvasively and used for the prediction of nodal metastasis. Methods Patients with lung cancer or suspected lung cancer who underwent EBUS‐TBNA were recorded prospectively and reviewed retrospectively. Both the B‐mode sonographic and elastographic findings were independently evaluated for each lymph node. The sonographic features were classified according to previously published criteria. If oval shape, indistinct margins, homogenous echogenicity, and the absence of coagulation necrosis sign were all observed by B‐mode imaging, then the lymph node was judged to be benign by sonographic imaging. In addition, if the stiffer area comprised more than 31% of the entire lymph node area, then the lymph node was judged to be malignant by elastography. We compared the results of these imaging‐based predictions with the pathological diagnoses. Results The prevalence of nodal metastasis was 78/228 (34.2%). B‐mode sonography predicted 95.8% of benign lymph nodes, and elastography predicted 72.1% of malignant lymph nodes. By combining the two modalities, 59 of 71 (83.1%) lymph nodes judged as malignant by both analyses were pathologically proven to be malignant, and 101 of 105 (96.2%) lymph nodes judged as benign by both analyses were pathologically proven to be benign. Conclusion The combination of elastography and sonographic findings showed good sensitivity and a high negative predictive value, which may facilitate selecting the most suspicious lymph nodes for biopsy. Key points Significant findings of the study. The combination of endobronchial elastography and sonography resulted in a higher diagnostic yield than either modality alone for predicting benign and malignant lymph nodes in patients with lung cancer. What this study adds. The combination of endobronchial elastography and sonography will help clinicians identify the most suspicious lymph nodes for puncturing during EBUS‐TBNA, which may improve the efficiency of EBUS‐TBNA.